Динамические режимы электромагнитного вибратора - Виштак, Т.В.; Кондратенко, И.П.; Ращепкин, А.П. (Технічна електродинаміка, 2011)
Methods of electromagnetic oscillator dynamic condition analysis depending on voltage, frequency, rigidity spring and friction sizes between billet and a mold are developed. Design of the offered electromagnetic oscillator with permanent magnets is described. Ranges of frequency change and amplitude of oscillator mobile part fluctuations are specified. The analysis of a dynamic status is executed on the basis of Kirchhoff and Dalamber equations system solution. Analytical interlinkage and electromagnetic force dependences on current value and displacement of the oscillator mobile part are established.